PENGARUH TERAPI BOARD GAME TERHADAP FUNGSI KOGNITIF PADA LANSIA DI PSTW SABAI NAN ALUIH SICINCIN TAHUN 2022 - Dini Qurrata Ayuni; Yenni Yenni; Rizka Nada Audiva (Ensiklopedia Education Review, 2022)
One of the health problems that often occurs in the elderly is a decline in cognitive function. According to the World Health Organization (WHO), in 2015, there were 35.6 million elderly people worldwide experiencing cognitive function disorders. Cognitive function includes the process of learning, perception, understanding, understanding, attention, and others, causing the reaction and behavior of the elderly to become slower. The prevalence of the elderly in Indonesia is included in the top five countries with the largest number of elderly people in the world, reaching 18.1 million people in 2010 to 28.8 million in 2020, or doubled (36 million) in 2025. West Sumatra Province has an elderly population reaching 44,403 people. In PSTW the population is 110. The purpose of the study was to determine the effect of playing the Dakon board game therapy on the cognitive function of the elderly.The research method is a quasi experiment using a pre and post test approach without a control design. This research was carried out at PSTW Sabai Nan Aluih Sicincin, the time of the study was from August-September 2022. The population in this study were all patients who were treated, totaling 110 people and the technique was sampling used purposive sampling. Collecting data by guided interviews, with the number of respondents 16 people. The data were then processed computerized and analyzed univariately in the form of frequency distribution and bivariate analysis using paired sample t test statistic test with p value < 0.05.The results showed that the average cognitive function before the intervention was 1.25 and after the intervention was 2.44. The result of p value obtained is 0.000, this means that there is a significant influence between cognitive function before and after the intervention.It is recommended for health workers at PSTW Sicincin to make this therapy as a procedure in overcoming the decline in cognitive function in the elderly. It is recommended for further researchers to continue this research using a control group.